The Künneth Formula for the Twisted de Rham and Higgs Cohomologies - Chen, K.-C.; Yu, J.-D. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
We prove the Künneth formula for the irregular Hodge filtrations on the exponentially twisted de Rham and the Higgs cohomologies of smooth quasi-projective complex varieties. The method involves a careful comparison of the underlying chain complexes under a certain elimination of indeterminacy.